Accumulated temperature requirements of Echinochloa crus‐galli seed‐setting: A case study with populations collected from rice fields. Issue 2 (13th June 2022) - Chen, Guoqi; Chen, Yang; Yu, Hang; Zhou, Lin; Zhuang, Xiangxin
Abstract: Effective accumulated temperature (EAT) is a basic index to predict plant growing and development, while EATs for key stages during Echinochloa crus‐galli seed‐setting are still unclear. We collected three E. crus‐galli populations (Nanling [NL], Feidong [FD], and Sihong [SH]) from different rice fields in eastern China and conducted four sets of pot experiments in a greenhouse. Plants of the three populations sown on May 9–12, averagely reproduced 484–671 mature seeds per plant; showed a duration of 67–76 days from sowing to heading, with an average EAT of 1, 156–1, 274°C; showed a duration of 90–94 days from sowing to seeds starting maturation in plant individuals with average EATs about 1, 571–1, 647°C; and showed a maturation stage lasting for 14–36 days. Significant negative correlations ( p < .01) were found between the period of collecting day after seed maturation and the number or 1, 000‐seed weight of mature seeds collected on the day, in each set of experiment. Compared with NL individuals sown on May 9, NL individuals sown on April 10 needed significantly higher EATs for periods from sowing to seed maturation, and from heading to seed maturation. According to logistic regressions, duration days needed for 50% of seeds to mature were 93–122 days after sowing, with EATs of 1, 625–1893°C for these E. crus‐galli populations. This study revealed EATs for E. crus‐galli seed‐setting, which suggested time windows for panicle‐removing control of E. crus‐galli in rice fields.